Assessment of nanoparticles and metal exposure of airport workers using exhaled breath condensate. (13th July 2016) - Marie-Desvergne, Caroline; Dubosson, Muriel; Touri, Léa; Zimmermann, Eric; Gaude-Môme, Marcelline; Leclerc, Lara; Durand, Catherine; Klerlein, Michel; Molinari, Nicolas; Vachier, Isabelle; Chanez, Pascal; Mossuz, Véronique Chamel
Abstract: Aircraft engine exhaust increases the number concentration of nanoparticles (NP) in the surrounding environment. Health concerns related to NP raise the question of the exposure and health monitoring of airport workers. No biological monitoring study on this profession has been reported to date. The aim was to evaluate the NP and metal exposure of airport workers using exhaled breath condensate (EBC) as a non-invasive biological matrix representative of the respiratory tract. EBC was collected from 458 French airport workers working either on the apron or in the offices. NP exposure was characterized using particle number concentration (PNC) and size distribution. EBC particles were analyzed using dynamic light scattering (DLS) and scanning electron microscopy coupled to x-ray spectroscopy (SEM-EDS). Multi-elemental analysis was performed for aluminum (Al), cadmium (Cd) and chromium (Cr) EBC contents. Apron workers were exposed to higher PNC than administrative workers ( p   <  0.001). Workers were exposed to very low particle sizes, the apron group being exposed to even smaller NP than the administrative group ( p   <  0.001). The particulate content of EBC was brought out by DLS and confirmed with SEM-EDS, although no difference was found between the two study groups. Cd concentrations were higher in the apron workers ( p   <  0.001), but still remained very low and close to the detection limit. Our study reported the particulate and metal content of airport workers airways. EBC is a potential useful tool for the non-invasive monitoring of workers exposed to NP and metals.